ANALYSIS OF REGULATIONS AND POLICIES IN THE EXPANSION OF LEGAL LIABILITY OF HOSPITALS IN INDONESIA - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
This article analyses the regulations and policies that contribute to the expansion of hospitals' legal responsibilities in Indonesia, with a focus on protecting patients' rights and improving the quality of health services. The main regulations that direct such legal responsibilities include Law No. 44/2009 on Hospitals and Law No. 36/2009 on Health, which regulate service standards and hospitals' obligations to ensure patient safety and security. In addition, a hospital accreditation system was also introduced as an effort to ensure high service quality and minimise legal risks. However, the implementation of these regulations faces challenges in the field, with some hospitals still experiencing difficulties in meeting the set standards, especially in resource-constrained regions. This study concludes that increased supervision, stronger regulatory support, and comprehensive education strategies are needed to improve compliance and quality of hospital services in Indonesia, so as to provide safe, quality, and equitable health services for the entire community.